MODERN PARTNER MARKETING TOOLS ON THE B2B MARKET - TSYBKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article describes modern tools that will help increase the success of marketing partnerships, based on the experience of leading Ukrainian enterprises in the development and implementation of marketing strategies of partner channels that have already achieved certain results. The key elements of a successful marketing partnerships strategy are covered, from identifying target partners and creating compelling value propositions to training and tracking campaign performance. The main performance indicators and key advantages for the marketing partnerships strategy are defined. Marketing materials that play a decisive role in attracting potential customers are indicated, and effective tactics of partnerships in digital marketing are also revealed. The study of modern partner marketing tools in the B2B market helps to study partnership strategies and their impact on the success of enterprises, providing ample opportunities for improving their management and achieving new business partnerships. Thanks to these tools, companies can effectively cooperate with other players in the market, expanding the customer base, increasing sales and profitability of enterprises.